Fracture Analysis of basement rock: A case example of the Eastern Part of the Peninsular Malaysia. (30th January 2015) - Shamsuddin, A; Ghosh, D
Abstract: In general, reservoir rocks can be defined into carbonates, tight elastics and basement rocks. Basement rocks came to be highlighted as their characteristics are quite complicated and remained as a significant challenge in exploration and production area. Motivation of this research is to solve the problem in some area in the Malay Basin which consist fractured basement reservoirs. Thus, in order to increase understanding about their characteristic, a study was conducted in the Eastern part of the Peninsular Malaysia. The study includes the main rock types that resemble the offshore rocks and analysis on the factors that give some effect on fracture characteristic that influence fracture systems and fracture networks. This study will allow better fracture prediction which will be beneficial for future hydrocarbon prediction in this region.